Answer:
it is -12
Step-by-step explanation:
Answer:
A. y = -16
Step-by-step explanation:
Hello!
What we do to one side of the equation we have to do to the other.
y + 7 = -9
We have to get y by itself so we have to get rid of the seven by doing the opposite of what it says
The opposite of addition is subtraction so we subtract 7 from both sides
y + 7 - 7 = -9 - 7
Solve
y + 0 = -16
Simplify
y = -16
The answer is A. y = -16
Hope this helps!
The answer is D (y+10)(y-6)
because
A. (−3, 3)
<span>3x – 4y = 21
</span>3(-3) - 4(3) = 21
-21 = 21 >>>>> not equal
B. (−1, −6)
<span>3(-1) - 4(-6) = 21
</span>21 = 21 >>>>>>>>>>Equal
C. (7, 0)
<span>3(7) - 4(0) = 21
</span>21 = 21>>>>>>>>>>equal
D. (11, 3)
<span>3(11) - 4(3) = 21
</span>21 = 21 >>>>>>>>>equal
First of all not to be rude, but it is order of operations not properties of operations. Second, you can solve equations by going in the order of PEMDAS or Parentheses, Exponents, Multiplication, division, addition, and subtraction. Multiplication and division are switchable, addition and subtraction. If you do not follow this order you get the equation or inequality wrong.